Discrete element modelling of jointed rock masses under dynamic loading - Chen, Shou Gen. (2008)
The discrete element method (DEM) is an effective numerical approach to solve discontinuous problems such as jointed rock masses. It has been widely used to model static problems, for example, rock slope, underground excavation and support. However, the application of the DEM in dynamic problems especially in explosion problems is relatively new, because of difficulties in determining the dynamic material properties, the explosion loading and other influence factors. This study is intended to investigate the response of jointed rock masses under explosion loading by using the Universal Distinct Element Code (UDEC) and correlating with the field explosion test.